Rebecca's Reward - Snelling, Lauraine (Minneapolis, Minn. : Bethany House, 2008)
Having experienced more than her share of sorrow, nineteen-year-old Rebecca Baard is now afraid to open her heart to love, but when her friends set out to help, she discovers that the best of intentions cannot keep events from taking a surprising turn.